English Language Exposure of Students in Visayas State University (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
The purpose of this study was to determine the level of language exposure toward the learning of the English language of the students in the Visayas State University. A learners’ exposure to the target language does have impact in language learning. Adapting a language exposure questionnaire, the researcher identified the activities that exposed students to the target language. With a scoring guideline, the researcher revealed the level of students’ exposure to the English language. Results of the study showed that more than half of the respondents have a moderate level of language exposure. Students were exposed most to the English language when they are at school or with the use of different media compared to when they are at home or communicating with friends. This result can be utilized both by teachers and students in engaging to appropriate activities both inside and outside the classroom that can help increase the learning of the English language.